2021
DOI: 10.1002/ps.6673
|View full text |Cite
|
Sign up to set email alerts
|

The potential of dimetindene maleate inducing resistance to blast fungus Magnaporthe oryzae through activating the salicylic acid signaling pathway in rice plants

Abstract: BACKGROUND: Rice blast disease (Magnaporthe oryzae) is considered the most destructive rice disease all over the world. Dimetindene maleate is used in medication against allergic reactions in humans. Dimetindene maleate used to induce systemic acquired resistance (SAR) in rice (Oryza sativa L.) in order to protect rice plants from blast disease. RESULTS: Dimetindene maleate was not effective against fungus linear growth in vitro. In glasshouse conditions, dimetindene maleate significantly improved resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…ISR often relies on pathways regulated by JA/ET. JaMYB and AOS2 are marker genes for JA-dependent signaling pathways, whereas ERF1 and ACS1 are markers of the ET signaling pathway ( Leonetti et al, 2017 ; Salman et al, 2022 ). Previous studies on rice have also shown that the exogenous application of plant hormones and antioxidants induces systemic defense against M. graminicola, and that the JA pathway plays a pivotal role in the induction of defense against RKN ( Nahar et al, 2011 ; Singh et al, 2020 ; Chavan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ISR often relies on pathways regulated by JA/ET. JaMYB and AOS2 are marker genes for JA-dependent signaling pathways, whereas ERF1 and ACS1 are markers of the ET signaling pathway ( Leonetti et al, 2017 ; Salman et al, 2022 ). Previous studies on rice have also shown that the exogenous application of plant hormones and antioxidants induces systemic defense against M. graminicola, and that the JA pathway plays a pivotal role in the induction of defense against RKN ( Nahar et al, 2011 ; Singh et al, 2020 ; Chavan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…PR1a and WRKY45 are markers of the SA signaling pathway and are major characteristic proteins of SAR ( Salman et al, 2022 ). WRKY45 and PR1a expression were increased in GC-7- and J2 + GC-7-treated plants compared to control and J2-treated plants at 1 dpi and 4 dpi, respectively, indicating that the defense response of rice to M. graminicola mediated by the SA signaling pathway was also activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fungal diseases inhibit the growth of rice, notably so rice blast disease caused by Magnaporthe oryzae [ 4 ], which reduces rice production by up to 30% annually around the world [ 5 ], which is enough rice for about 60 million people [ 6 ]. Fungal infection is a leading factor driving agricultural production shortfalls and in the dramatic growth in widespread lesions in immunosuppressed people [ 7 ]. Currently, disease control relies on the use of industrial chemicals such as fungicides [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rice is the most important food staple for more than half of the world’s population ( Salman et al., 2022 ). Rice blast, caused by Magnaporthe oryzae , is one of the most destructive rice diseases worldwide, which results in substantial crop loss and potential economic disaster.…”
Section: Introductionmentioning
confidence: 99%